CD40-mediated immune cell activation enhances response to anti-PD-1 in murine intrahepatic cholangiocarcinoma - Diggs, Laurence P.; Ruf, Benjamin; Ma, Chi; Heinrich, Bernd; Cui, Linda; Zhang, Qianfei; McVey, John C.; Wabitsch, Simon Franz Friedrich; Heinrich, Sophia; Rosato, Umberto; Lai, Walter; Subramanyam, Varun; et al. (Journal of hepatology, 2021)
Background & Aims - While cholangiocarcinomas (CCAs) commonly express programmed cell death 1 (PD-1) and its ligand (PD-L1), they respond poorly to immune checkpoint inhibitors (ICIs). We aimed to determine whether stimulating antigen-presenting cells, including macrophages and dendritic cells, using a CD40 agonist could improve this response. - Methods - We compared treatment responses in subcutaneous, orthotopic, and 2 plasmid-based murine intrahepatic CCA (iCCA) models. Mice were treated for 4 weeks with weekly IgG control, a CD40 agonistic antibody, anti-PD-1, or the combination of both (anti-CD40/PD-1). Flow cytometric (FACS) analysis of lymphocytes and myeloid cell populations (including activation status) was performed. We used dendritic cell knockout mice, and macrophage, CD4+ and CD8+ T cell depletion models to identify effector cells. Anti-CD40/PD-1 was combined with chemotherapy (gemcitabine/cisplatin) to test for improved therapeutic efficacy. - Results - In all 4 models, anti-PD-1 alone was minimally efficacious. Mice exhibited a moderate response to CD40 agonist monotherapy. Combination anti-CD40/PD-1 therapy led to a significantly greater reduction in tumor burden. FACS demonstrated increased number and activation of CD4+ and CD8+ T cells, natural killer cells, and myeloid cells in tumor and non-tumor liver tissue of tumor-bearing mice treated with anti-CD40/PD-1. Depletion of macrophages, dendritic cells, CD4+ T cells, or CD8+ T cells abrogated treatment efficacy. Combining anti-CD40/PD-1 with gemcitabine/cisplatin resulted in a significant survival benefit compared to gemcitabine/cisplatin alone. - Conclusion - CD40-mediated activation of macrophages and dendritic cells in iCCA significantly enhances response to anti-PD-1 therapy. This regimen may enhance the efficacy of first-line chemotherapy. - Lay summary - Checkpoint inhibition, a common form of immune therapy, is generally ineffective for the treatment of cholangiocarcinoma. These tumors suppress the infiltration and function of surrounding immune cells. Stimulating immune cells such as macrophages and dendritic cells via the CD40 receptor activates downstream immune cells and enhances the response to checkpoint inhibitors.